Influence of socio-economic status and marital satisfaction on domestic violence among couples living in Nigeria (2016)
Adversely, increase rate of conduct disorder, low self-esteem, low education standard, drug dependence/alcoholism and sexual risk behaviour among children from violent couples thereby becoming hazardous to themselves and society at large attracted the attention of this study to investigate factors predicting domestic violence. This study investigated influence of socioeconomic variables and marital satisfaction on domestic violence among couples in Nigeria. The study adopted cross sectional research design, purposive sampling technique was used to select 250 consisting of 112 males and 138 females who participated in the study and questionnaires was used for data collection. The results of the finding revealed that income significantly predicts domestic violence among couples in Nigeria. Further analysis revealed that there is significant influence of marital satisfaction on domestic violence. Therefore, it was concluded that income and marital satisfaction are predictors of domestic violence among couples in Nigeria and it is recommend that government and non-governmental organisation should endeavour to implement or boost effective poverty alleviation programmes that will alleviate poverty in our society